Interprétations de changements climatiques dans un village du Nord de la Thaïlande - Alexandre Marouen (Revue Internationale des Études du Développement)
Based on the anthropology of risks, this article studies the ways with which inhabitants of a Northern Thailand village interpret climate changes, through the case of a drought. The results of an ethnographic fieldwork reveal three main interpretations. The first one links the climate changes to a natural phenomenon, according to a Buddhist vision. The second one blames destructions of the environment caused by the inhabitants. The third one mentions misbehaviours towards immaterial entities. The villagers did not use the notion of the global climate change. Thus, they made sense of the climate changes through their own cultural references and the evolutions of their local environment.